Mode of Presentation of Liver Cirrhosis: A Study in a Tertiary Level Hospital (Faridpur Medical College Journal, 2021)
Liver cirrhosis is an important cause of death and disability globally. This cross-sectional study was carried out in Faridpur Medical College Hospital from November 2018 to April 2019 to see the patterns of clinical presentations and associated factors among admitted liver cirrhosis patients. A total of 89 patients were included. Data were collected by detailed history from patients or their relatives followed by thorough physical examination as well as diagnostic evaluation; then those were checked, verified for consistency and edited for result. Among total respondents, the majority were male (69.7%) with a male to female ratio of 1:0.44. Age of patients ranged between 22-106 years with mean age of 52.33 year. The patients predominantly presented with ascites (49.4%), gastrointestinal bleeding (27%), peripheral edema (24.7%), and encephalopathy (21.3%). The in-hospital case fatality rate was 11.2% and the patients presented with decreased urinary output, peripheral edema and encephalopathy had statistically significant death rate. The results of the study highlighted that the patients with liver cirrhosis mostly present with features of decompensation and there is a statistically significant relation with some of these clinical presentations with in-hospital mortality.Faridpur Med. Coll. J. 2021;16(1):39-41